2017
DOI: 10.1002/art.40186
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, Pharmacokinetics, and Pharmacodynamics of Filgotinib, a Selective JAK‐1 Inhibitor, After Short‐Term Treatment of Rheumatoid Arthritis: Results of Two Randomized Phase IIa Trials

Abstract: ObjectiveJAK inhibitors have shown efficacy in rheumatoid arthritis (RA). We undertook this study to test our hypothesis that selective inhibition of JAK‐1 would combine good efficacy with a better safety profile compared with less selective JAK inhibitors.MethodsIn two 4‐week exploratory, double‐blind, placebo‐controlled phase IIa trials, 127 RA patients with an insufficient response to methotrexate (MTX) received filgotinib (GLPG0634, GS‐6034) oral capsules (100 mg twice daily or 30, 75, 150, 200, or 300 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 38 publications
0
53
0
Order By: Relevance
“…RA is an autoimmune disorder, and although several therapeutics are approved for the treatment of patients with an inadequate response to methotrexate (MTX) or tumor necrosis factor inhibitors (anti-TNF) (3)(4)(5)(6)(7)(8)(9), some patients become refractory to currently available therapeutics and may benefit from therapy utilizing a different mechanism of action (6,(8)(9)(10)(11)(12).…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 99%
“…RA is an autoimmune disorder, and although several therapeutics are approved for the treatment of patients with an inadequate response to methotrexate (MTX) or tumor necrosis factor inhibitors (anti-TNF) (3)(4)(5)(6)(7)(8)(9), some patients become refractory to currently available therapeutics and may benefit from therapy utilizing a different mechanism of action (6,(8)(9)(10)(11)(12).…”
Section: Bruton's Tyrosine Kinase (Btk) and Fenebrutinibmentioning
confidence: 99%
“…Results of two other Phase IIa trials showed that filgotinib is generally well‐tolerated in RA subjects that had an insufficient response to MTX (Vanhoutte et al, 2017). This study was continued by two Phase IIb trials: randomized, dose‐finding study (DARWIN1; additive to MTX) and DARWIN2 (Single therapy; Alten et al, 2017).…”
Section: Clinical Developmentsmentioning
confidence: 99%
“…In two 4-week double blind, placebo controlled phase IIa trials [ 8 ], RA patients with an insufficient response to MTX received filgotinib daily, at doses ranging from 30 to 300 mg or placebo on top of MTX, to explore safety, efficacy, pharmacokinetics and pharmacodynamics. Early efficacy was noted from a dose of 75 mg daily upwards, and the pharmacokinetics of filgotinib and its JAK1 selective active metabolite was dose-proportional over the 30–300 mg range.…”
Section: Filgotinibmentioning
confidence: 99%